Determinación de la calidad del agua del río Jambelí, con bioindicadores (macroinvertebrados) en la parroquia el Chaupí cantón Mejía periodo 2019-2020. - Pilaguano Socasi, Katherine Mishell (2020)
The researching project was done in the El Chaupí town, in Mejía Canton, in Pichincha Province, in order to determine the quality of water, through bioindicators and physical, chemical and microbiological analysis, of Jambelí River. In the months of October to January, three samples were taken, where three strategic points of the river, a total of 1388 individuals classified in 7 orders, 12 families and 13 genres were counted. Water quality indices for macroinvertebrates (EPT) Ephemeroptera, Plecoptera, Trichoptera, (BMWP / Col.) Biological Monitoring Working Party, (ABI) Andean Biological Party, Shannon-Weaver for species diversity and for physical analysis were calculated, chemical and microbiological, ICA was used. (NFS) “Water Quality Index” National Sanitation Foundation, in composite samples collected in November and January. The results obtained by applying the nine parameters of the ICA. (NFS) determined that the water quality is Media with an average of 52.11, which were compared with the Current Ecuadorian Legislation - TULSMA, where it was evidenced that they meet the maximum permissible limits. In the same way, when applying the techniques of the EPT indexes with 39%, BMWP / Col with a score of 56 and ABI with 48 it was defined the water quality corresponds to moderately contaminated waters. The Shannon-Weaver index indicates that the average amount of species diversity is 1,465 corresponding to low diversity, according to the Staub scheme it indicates moderate pollution.